(untitled) - Davidek, Jiri (The Netherlands, 1990)
The book deals with the chemical reactions taking place in food during industrial processing and storage, and shows how various food components react according to their chemical composition and the influence of other components or processing conditions. The work describes in detail the changes of the main food components (proteins, saccharides, lipids) and of other components important from the standpoint of the nutritional, sensory and hygienic properties of food materials. Important changes of physical properties (which may affect the chemical reactivity) are given as well. The most important reactions are elucidated on examples from technological processes which also show the effect of these chemical reactions on the
Keywords: Food,Food,Food industry and trade; Analysis,Quality,Quality control